Antimicrobial Properties of Fenugreek Seeds against Skin Infection Causing Bacteria - Seviar, Shirlin Ros (2017)
Spices such as fenugreek seeds are acknowledged as medicinal plants because they are capable of inhibiting the growth of various staphylococcal species such as S. aureus and S. epidermidis. In this study, boiled and methanolic seed extracts in different concentrations were tested against acne and pimple causing bacteria namely P. acnes, S. aureus and S. epidermidis using agar-well diffusion and disc diffusion techniques. The antimicrobial activity of the fenugreek seed was determined through the formation of the zones of inhibition (mm) and it was confirmed that boiled seed extract was most effective against S. aureus in 150g/200mL water based on the ANOVA test result. The methanolic seed extract was most effective against P. acnes based on the significant increase in diameter of zone of inhibition and the most effective concentration was 2.0mg/mL according to ANOVA test result. The study proved that boiled and methanol seed extracts have good antimicrobial effects against S. aureus, P. acnes and S. epidermidis with methanolic extracts having a better antimicrobial response against these bacteria. It was also proven that increasing concentration of boiled and methanolic extracts corresponded to an increasing antimicrobial activity of the seed extracts against the bacteria. Therefore, this study could lead to future use of fenugreek seeds against skin pathogens.